Research progress of construction and application of nursing studio (护理工作室的应用及研究进展) - YU Lin (喻琳); LI Guirong (李桂蓉) (Association of Integrative Nursing, 2021)
This paper reviewed studies on construction and application of nursing studio from the perspectives of concept, origins, development, research status, pros and cons, in order to provide reference for the development of nursing studio in China. (本文总结护理工作室的应用及研究进展, 从护理工作室的概念、起源、发展、国外内护理工作室的研究现状、优势与不足等方面进行综述, 旨在为国内开展护理工作室工作提供借鉴。)